2018
DOI: 10.1186/s13018-018-0761-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary total knee arthroplasty using constrained condylar knee design for severe deformity and stiffness of knee secondary to post-traumatic arthritis

Abstract: BackgroundKey to a successful outcome of total knee arthroplasty (TKA) is to attain optimum alignment, adequate balance, and deformity correction. In primary TKA, this can be achieved efficiently by posterior stabilized (PS) design with or without the sub-periosteal release. However, certain circumstances such as post-traumatic arthritis are often associated with severe deformities with a significant bone defect, stiffness, and instability. Such deformities are extremely difficult to balance with soft tissue r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…Rai et al. (2018) found similar implant survival (95%) to our study and with a high complication rate for CCK. CCK used by Sabatini et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Rai et al. (2018) found similar implant survival (95%) to our study and with a high complication rate for CCK. CCK used by Sabatini et al.…”
Section: Discussionsupporting
confidence: 89%
“…(2017) and Rai et al. (2018)found a high number of patients with intraoperative complications such as fractures and ligament injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, concerns for using constrained implants in TKA are related to the increased stress at the bone-cement-implant interface as well as the sacrifice of more bone, which have been associated with higher risk for aseptic loosening and revision [ [13] , [14] , [15] ]. However, several studies have still demonstrated favorable outcomes for constrained TKA implants at the index surgery, if indicated [ [16] , [17] , [18] ]. Nonconstrained implants should be considered in Blount disease with less severe deformities; however, it should be noted that in the report by Natoli et al., 2 of the 6 knees in that series that underwent the surgery without constrained components were subsequently revised to hinge components [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, the consequence of that behaviour will be a higher number of patients coming in at later stage with more pronounced bony defects and deformities and due to that more difficult to treat. This can also have an impact on the outcome and on the complication rate 5,6 . Keeping in contact with patients (i.e.with the help of digital platforms, such as video consultation) is one option to help them through this time but also to give them a time line for their postponed surgery.…”
Section: Role As a Surgeonmentioning
confidence: 99%